Air cooled heat pump coupled with Horizontal Air-Ground Heat Exchanger (HAGHE) for Zero Energy Buildings in the Mediterranean climate. (December 2017) - Baglivo, Cristina; Congedo, Paolo Maria; Laforgia, Domenico
Abstract: This study demonstrates how it is possible to increase the performances of an air-cooled heat pump by the use of Horizontal Air-Ground Heat Exchanger (HAGHE); the analysis has been carried out varying the air flow rate and heat conductivity of the ground. For a warm climate, the air treatment using HAGHE involves an improvement of the Energy Efficiency Ratio (EER) of the heat pump for the entire summertime. About the wintertime, the coefficient of performance (COP) results improved from November to February, but it is possible to install a by-pass to permit to the heat pump to work at the best conditions.